Active metal brazing of Al2O3 to Kovar® (Fe–29Ni–17Co wt.%) using Copper ABA® (Cu–3.0Si–2.3Ti–2.0Al wt.%). Issue 3 (22nd January 2018) - Ali, Majed; Knowles, Kevin M.; Mallinson, Phillip M.; Fernie, John A.
Abstract: The application of an active braze alloy (ABA) known as Copper ABA® (Cu–3.0Si–2.3Ti–2.0Al wt.%) to join Al2 O3 to Kovar® (Fe–29Ni–17Co wt.%) has been investigated. This ABA was selected to increase the operating temperature of the joint beyond the capabilities of typically used ABAs such as Ag–Cu–Ti-based alloys. Silica present as a secondary phase in the Al2 O3 at a level of 5 wt.% enabled the ceramic component to bond to the ABA chemically by forming a layer of Si3 Ti5 at the ABA/Al2 O3 interface. Appropriate brazing conditions to preserve a near-continuous Si3 Ti5 layer on the Al2 O3 and a continuous Fe3 Si layer on the Kovar® were found to be a brazing time of ≤15 min at 1025 °C or ≤2 min at 1050 °C. These conditions produced joints that did not break on handling and could be prepared easily for microscopy. Brazing for longer periods of time, up to 45 min, at these temperatures broke down the Si3 Ti5 layer on the Al2 O3, while brazing at ≥1075 °C for 2–45 min broke down the Fe3 Si layer on the Kovar® significantly. Further complications of brazing at ≥1075 °C included leakage of the ABA out of the joint and the formation of a new brittle silicide, Ni16 Si7 Ti6, at the ABA/Al2 O3 interface. This investigation demonstrates that it is not straightforward to join Al2 O3 to Kovar® using Copper ABA®, partly because the ranges of suitable values for the brazing temperature and time are quite limited. Other approaches to increase the operating temperature of the joint are discussed.